Bacterial Diversity of Active Sludge in Wastewater Treatment Plant - Jiang, X.; Ma, M.; Li, J.; Lu, A.; Zhong, Z.
A bacterial 16S rDNA gene clone library was constructed to analyze the bacterial diversity of active sludge in Gaobeidian Wastewater Treatment Plant, Beijing. The results indicated that the bacterial diversity of active sludge was very high, and the clones could be divided into 5 different groups. The dominant bacterial community was proteobacteria, which accounted for 76.7
Keywords: ACTIVE SLUDGE; MICROBIAL MOLECULAR ECOLOGY; 16S RDNA CLONE LIBRARY; BACTERIAL DIVERSITY; GAOBEIDIAN WASTEWATER TREATMENT PLANT